Evaluation of microbial quality and pathogenic potentiality of enterobacteria in poultry feeds (Journal of Bio-Science, 2019)
The present investigation has been carried out to assess the microbial safety and pathogenic potentialities of enterobacteria in poultry feeds. From the results it was observed that total aerobic plate count of poultry feeds samples were recorded as 2.8 × 105 to 5.8 × 109 cfu/g and 100% samples contained ≥106 cfu/g while the highest mean of cfu was counted as log10 8.797/gm. Large number of coliforms were recorded in different poultry feed samples and the ranges of cfu were counted as 1.2 × 104 to 5.2 × 107/g while average 75% samples were contaminated with coliform bacteria with ≥104 cfu/g and the highest mean of cfu was counted as log10 6.103/g. The ranges of cfu of Escherichia coli were 1.03 × 102 to 1.09 × 105/g and 70% samples contained ≥102 cfu/g while the highest mean of cfu was counted as log10 4.493/gm. But the ranges of cfu of total Salmonella sp. were recorded as 1.02 × 101 to 5.25 × 104/g and 50% samples contained ≥102 cfu/g and the highest mean of cfu was counted as log10 3.665/g. Total 29 enterobacterial isolates were isolated from the feed by using selected media. On the basis of morphological characteristics and biochemical test results the isolates were identified as Salmonella sp., Shigella sp., Klebsiella sp., Citrobacter sp., Proteus sp., Enterobacter sp. and Escherichia coli. These isolates were tested on blood agar medium and only seven isolates showed positive β-hemolytic activity.In virulence efficacy test, only hemolytic positive isolates were ingested to chicken and observed that E. coli (SGE-1), Klebsiella sp. (SSE-6) and Salmonella sp. (JSS-9) isolates were highly toxic because the experimental chickens were died after 3 days of ingestion of the bacteria, two isolates showed loose motion symptom after 15 days while other isolates showed little sickness. All the selected isolates showed positive hem-agglutination reactivity in poultry RBC. The results indicate that the poultry feeds were highly contaminated with pathogenic enterobacteria which are risk to public health.J. bio-sci. 28: 59-68, 2020